Mechanisms underlying reductions in stroke volume at rest and during exercise at high altitude. Issue 5 (3rd July 2016) - Stembridge, Mike; Ainslie, Philip N.; Shave, Rob
Abstract: High-altitude exposure challenges the cardiovascular system to maintain oxygen delivery to the mitochondria under conditions of hypoxic stress. Following acclimatisation (3–5 days), stroke volume (SV) falls to below sea-level values but heart rate remains elevated, such that cardiac output is maintained compared to sea level. The decrease in SV has been a topic of research for over 40 years, but the underlying mechanisms are incompletely understood. Impaired systolic contractile function secondary to reduced coronary arterial oxygen tension has been investigated as a potential cause for the decrease in SV. However, despite in vitro evidence of impaired cardiac contractile force in severe hypoxia, the majority of studies to date have reported enhanced in vivo ventricular systolic function at rest and during exercise in humans up to and above 5000 m. However, the elevated function observed at rest has recently been suggested to reduce the functional reserve available during exercise. While in vivo systolic function appears enhanced at high altitude, a decrease in left ventricular end-diastolic volume (EDV) and altered filling patterns of both ventricles has been observed. The reduction in ventricular filling will undoubtedly affect SV, and four potential mechanisms have been proposed to explain the reduction in left ventricular filling. In this article, both historical and recent reports of systolic function at high altitude will be reviewed, and evidence supporting and refuting each of the four mechanisms underpinning reduced left ventricular filling will be discussed.